ANALYSIS OF MATERIAL INVENTORY CONTROL THE METROSTATER CONSTRUCTION PROJECT IN DEPOK - Kohar, Sulistyadi; Dana, I Nyoman; Agung, Wardana; Nurasyiah, Anna (Sustainable Environmental and Optimizing Industry Journal, 2022)
In the last 10 years the construction sector boom has increased rapidly. The Government's Long-Term Plan and the leniency of government policies on investors wishing to invest in Indonesia have stimulated the growth of the construction sector in Indonesia. Increasingly adequate infrastructure encourages entrepreneurs or contractors to invest in public and private projects. One of the private construction projects being handled is the Depok Metrostater Project. This project is located in the city of Depok which has a Transit Oriented Development (TOD) concept. Currently the project is still in the construction stage of the foundation and in its implementation it requires concrete iron as raw material. To ensure material availability, the contractor will perform a scheduled recapitulation of materials according to usage needs. This material scheduling implements material stock inventory control that must be available in the warehouse, so as not to overstock. For this reason, an optimal inventory control analysis is needed through the Economic Order Quantity (EOQ) method, Lot For Lot, Fixed Period Requirement (FPR), and the Wagner and Within algorithms. The comparative results of the inventory method analysis based on the Wagner and Within Algorithm methods provide the most economical results with the minimum total cost of Rp. 583,466,945, - among the other three methods. and Contractors can make efficiency by 35%